Pandangan Fukaha Klasik dan Kontemporer Tentang Wakaf Temporer - Waluya, Atep Hendang (Salam (Islamic Economics Journal), 2025)
Wealth is the pillar of human life, with it humans can live nobly and become a muhsinin. With wealth, difficulties will be overcome and complex problems can be solved, changes in the era are overcome, wealth is a support for technology and industry, the advancement of science and knowledge. Waqf is a form of worship that has a broad social effect, but there are still many people who are not familiar with waqf and its various types, such as temporary waqf. The purpose of this article is to find out the views of both classical and contemporary jurists regarding the validity and permissibility of temporary waqf. Literature study is the method used in writing this article. Data collection was carried out by searching for literature related to the theme discussed. The data analysis used uses text and discourse analysis. All fukaha agree that permanent waqf is valid and prescribed. As for temporary waqf according to the majority of classical jurists, it is not permissible, because the waqf is required to be tabīd. As for the Maliki School and a small number of other classical jurists, they are of the opinion that temporary waqf is valid and permitted. Among the contemporary scholars who are of the opinion that temporary waqf is valid, permissible and prescribed are al-Dubyān, al-Khatlān, Yūnus al-Miṣrī, Hānī Manṣūr, Aḥmad al-Afnadī, Sayyid ‘Ismā‘īl, the authors of al-Fiqh al-Muyassar and it is an opinion that is selected by the AAOIFI.